Arabic and Indonesian Islamic Literature: A Comparative Study of Aesthetics, Genres, and Cultural Acculturation - Muhammad Fadhlurrahman Zakaria; Sukron Kamil; Muhammad Alfa Choirul Murtadho (Institut Agama Islam Negeri Metro, 2026)
Islamic literature has served as an important medium for expressing tawhid, spirituality, and Muslim cultural identity across diverse societies. This study examines the historical development of Islamic literature in Arabic and Indonesian traditions by comparing their aesthetics, themes, and Islamization strategies. Using a comparative literary approach and descriptive-qualitative library research, the study analyses poetry, prose, hikayat, suluk, and modern Islamic literary works from both traditions. The findings show that Arabic Islamic literature evolved from classical Sufi poetry into contemporary ideological narratives marked by theological complexity, while Indonesian Islamic literature developed through cultural acculturation reflected in hikayat, gurindam, and adaptive popular literature. Although both traditions share transcendental orientations and function as instruments of Islamic dissemination, they differ in aesthetic expression, symbolic structure, and the intensity of Sufi influence. The originality of this study lies in its comparative mapping of the historical and aesthetic intersections between Arabic and Indonesian Islamic literature, contributing to Islamic cultural literacy and cross-cultural literary studies.